Analysis of Mechanical Properties of Functional Parts of Goat Hoofs under Multi-Slope - Zhang, Fu; Wang, Xinyue; Cui, Xiahua; Qiu, Yubo; Teng, Shuai; Ali, Shaukat; Fu, Sanling (Agriculture (Basel), 2024)
In order to improve the adhesive and passing performance of agricultural tracked vehicles under a non-structural environment, a theoretical design method of the structure of a bionic track pattern is proposed in this article. The Saanen goat is taken as the experimental subject, and the hoof tips and hoof spheres are taken as the characteristic functional parts, whose pressure is measured by thin film pressure sensors. The Qualisys Track Manager (QTM) gait analysis system was used to obtain the gait sequence of goats under multi-slope. The changes in vertical ground reaction force (GRF) and vertical impulse (VI) of the hoof tips and spheres and adhesion coefficient under multi-slope were analyzed. The results show that with the increase in slope, the GRF is transferred from the left hind hoof to the right front hoof, and the right front hoof has the most significant effect. Under the 10-degree slope, the peak vertical GRF and VI of the inner tip of the right front hoof are the largest; peak vertical GRF is 146.20 N, and VI is 127.67 N·s. The adhesion coefficient is the largest; the right front and left hind hoof are in the diagonal two-phase supported state, and μ is 0.3455. Therefore, the inner tip of the right front hoof is used as a bionic prototype to design the track pattern architecture. It provides a theoretical basis for the design and optimization of bionic patterns applied to agricultural tracked vehicles.